PENGARUH BENTUK MATA PANCING DAN PENGGUNAAN UMPAN TERHADAP HASIL TANGKAPAN IKAN KEMBUNG (RASTRELLIGER SP) DI PERAIRAN CILACAP - Prakoso, Dito Ragil; M.Pi., Pramonowibowo; Sardiyatmo, Dr. (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Rastrelliger Fish fishing in general use fishing stalling (Handline). This is because Rastrelliger Fish were caught with fishing stalling condition is good and fresh so it has a high selling price. The use of bait and hook size that effectively would provide good catches. Therefore, the need for a scientific study on the use of bait and hook sizes different to catch “Ikan Kembung”(Rastrelliger sp.).The purpose of this research was to analyze Rastrelliger Fish (Rastrelliger sp.) catches on the use of bait and hook shapes which different interaction between the use of the hook and the kind of bait to catch “ Ikan Kembung” (Rastrelliger sp.).The research uses experimental fishing with 2 variables are the type of bait and hook shape with 4 treatments are “(Tembang, squid, double hook and single hook). Each performed with 10 replications.Data analysis using data normality test and ANOVA with SPSS 17.0.The result showed that differences “Tembang Lures” and bait squid in this research affect the amount of proceeds Rastrelliger Fish (Rastrelliger sp.) catches. It is seen from the catch of squid bait with hook double hook as many as 48 tails and bait the hook” Tembang” with double hook as many as 37 tails, squid and bait the hook with a single hook as many as 35 tails and the “Tembang” with the hook bait hook single by 29 tail. ANOVA test result showed that, where using a combination of fishing gear and bait squid hook double hook size well used.